2014
DOI: 10.1186/2049-6958-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Treating severe allergic asthma with anti-IgE monoclonal antibody (omalizumab): a review

Abstract: Increased asthma severity is not only associated with enhanced recurrent hospitalization and mortality but also with higher social costs.Several cases of asthma are atopic in nature, with the trigger for acute asthma attacks and chronic worsening of inflammation being allergens inducing an immune, IgE mediated response.Anti-inflammatory treatments are effective for most of asthma patients, but there are subjects whose disease is incompletely controlled by inhaled or systemic corticosteroids and these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 54 publications
1
36
0
1
Order By: Relevance
“…Omalizumab treatment significantly improves symptoms and disease control, reduces asthma exacerbations, and increases patients’ quality of life [22]. Our study corroborates these findings, but also shows that omalizumab is helpful for severe chronic asthma caused by seasonal allergens.…”
Section: Discussionsupporting
confidence: 85%
“…Omalizumab treatment significantly improves symptoms and disease control, reduces asthma exacerbations, and increases patients’ quality of life [22]. Our study corroborates these findings, but also shows that omalizumab is helpful for severe chronic asthma caused by seasonal allergens.…”
Section: Discussionsupporting
confidence: 85%
“…Phase III trials with study periods up to 12 months have shown omalizumab to reduce the frequency of asthma exacerbations and concomitant medication burden and improve symptom severity and quality of life, while also being safe (12)(13)(14)(15). Efficacy and safety data from these and subsequent studies have been reviewed elsewhere (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) A meta-analysis of eight randomized trials (n = 3429) showed that omalizumab therapy was associated with a greater likelihood of withdrawal from corticosteroid therapy (relative risk [RR] = 1.80, 95% CI = 1.42-2.28, P < 0.0001) and a lower risk of exacerbations at the end of the stable (RR = 0.57, 95% CI = 0.48-0.66, P = 0.0001) and the adjustable-steroid phases (RR = 0.55, 95% CI = 0.47-0.64, P = 0.0001) (26).…”
Section: Introductionmentioning
confidence: 99%
“…Airway allergies are largely type 1 hypersensitivity reactions, and they are characterized by elevated levels of systemic allergen-specific IgE antibodies and hyperreactivity of the airway tract [3]. Medications such as anti-IgE therapy, and anti-histamines, which can be administered orally or systemically via injections are available for short term relief [4, 5]. However, allergen specific immunotherapy (ASI) is the only approach to treat allergies permanently [6].…”
Section: Introductionmentioning
confidence: 99%